Electromagnetic adverse radiation monitoring system using the QIVICON platform - Романова, Анна Віталіївна; Конахович, Георгій Филимонович (Ukrainian Information Security Research Journal, 2020)
In this article it was explained how a harmful signal could be intruded into the sensor system remotely. The structure of the sensor, which was considered vulnerable to electromagnetic interference, has been presented. Demonstrated the way of how the microcontroller and other components of the sensor work. The exact explanation was given to determine exact ways how the proposed sensor works in the presence of an attack signal. Examples were given of how the attack detection system changes with respect to the type of physical quantity measured by the sensor. It was presented in detail how the proposed method of protection works and its safety was analyzed. Hereby shown how to keep a certain security guarantee. A new method of protection for attack detection has been proposed, which is based on the idea that when the sensor is turned off, the sensor output should be "quiet". If the attack signal is maliciously induced into the sensor system during the "quiet" period, the microcontroller can detect it. A detailed description of the method of detecting EMC (electromagnetic interference) is presented and the guarantee of their detection in the context of a strong model of an attacker is proved. Such approach for detecting common EMF signals can exist both in a microphone system and in a system of temperature sensors or other sensors. It was explained what Manchester coding is and was shown in the graph, how and why it was used in this work. It shows which parts and components of the sensor systems were vulnerable to attacks and explains how these components could have been protected in the near future. It has been proven that the detection mechanism presented in the paper is both effective and reliable. The proofs were based only on theoretical calculations; however, they include all possible deviations. The subject focus was concentrated on the attacks with powerful EMCs, in which an attacker manipulates the user's sensors to enter exactly the values he wants.